Quantification of radionuclide distribution and migration during Cu-(Fe)-sulphide mineral processing by alpha particle autoradiography. (March 2021) - Kalnins, Christopher A.G.; Ottaway, David; Cook, Nigel J.; Spooner, Nigel A.
Abstract: Understanding the movement of radionuclides (RNs) between different mineral hosts during processing of base metal ores is critical for accurate modelling of RN deportment and optimisation of processes designed to reduce or eliminate RNs. Here, we demonstrate that spatially resolving quantitative alpha particle autoradiography combined with backscatter electron imaging and energy dispersive X-ray spectroscopy (EDS) can establish the correlation between alpha-emitting RNs (notably 226 Ra and 210 Po, daughters of the abundant 238 U decay series) and certain minerals, in different stages of processing. This is achieved by locating the RNs to a specific mineral grain, the species of which can subsequently be identified using EDS. The mineralogy of RN-associated grains can then be compared with the mineral suite and relative abundances of the species within the sample, by relating how often each mineral is associated with alpha decay-events. In the processing of uranium-bearing copper ores, migration of alpha-emitting RN daughters of the 238 U series were observed, and these RNs were demonstrated to correlate strongly with barite, bornite and covellite over other coexisting minerals. Highlights: Alpha-particle autoradiography can locate alpha-emitting radionuclide bearing grains at micron-scale spatial resolution. The associations of radionuclides with specific minerals were quantified. Radionuclide migration was traced through sequential mineral processing stages. Alpha-particle emitting radionuclides were incorporated in Cu-(Fe)-sulphides during sulphide leaching.